Financial appraisal of farm investments - Agricultural Refinance Coroporation (Bombay : Agricultural Refinance Coroporation, 1971)
This book examines financial appraisal of farm investments with focus on stages of appraisal work; methods of estimating incremental income: importance of regional norms; and appraisal schedules.
lje 25/1/19
Loans
Keywords: Financial appraisal; Agriculture